2018
DOI: 10.1002/lary.27111
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind, placebo‐controlled study with alginate suspension for laryngopharyngeal reflux disease

Abstract: 2. Laryngoscope, 128:2252-2260, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…15,16 Alginates are natural polysaccharides that form a raft on top of the gastric contents to generate a mechanical barrier, thereby preventing reflux outside the stomach, and reducing or preventing the contact of gastric contents with the esophageal and laryngeal mucosa. [16][17][18] Moreover, an in vitro study has shown that alginate has an inherent ability to effectively inhibit the enzymatic action of pepsin and to protect human esophageal mucosa against acid-induced damage for a prolonged period after application. [17][18][19] Another relevant therapeutic agent in the current context is hyaluronic acid, which also has a mucoadhesive effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Alginates are natural polysaccharides that form a raft on top of the gastric contents to generate a mechanical barrier, thereby preventing reflux outside the stomach, and reducing or preventing the contact of gastric contents with the esophageal and laryngeal mucosa. [16][17][18] Moreover, an in vitro study has shown that alginate has an inherent ability to effectively inhibit the enzymatic action of pepsin and to protect human esophageal mucosa against acid-induced damage for a prolonged period after application. [17][18][19] Another relevant therapeutic agent in the current context is hyaluronic acid, which also has a mucoadhesive effect.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Moreover, an in vitro study has shown that alginate has an inherent ability to effectively inhibit the enzymatic action of pepsin and to protect human esophageal mucosa against acid-induced damage for a prolonged period after application. [17][18][19] Another relevant therapeutic agent in the current context is hyaluronic acid, which also has a mucoadhesive effect. However, our literature review found that the effect of hyaluronic acid on the laryngeal mucosa in the context of LPR has not been studied to date.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 15 placebo RCTs, two trials were excluded from the analysis because the treatment was only based on alginate; one study was excluded due to use of voice therapy in addition to PPIs . Two studies were considered as inadmissible due to insufficient information in the publications (i.e., percentage of patients who had > 50% of symptoms improvement) .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 72 qualified articles, we found 15 placebo RCTs, 13 prospective controlled trials (with or without randomization), 40 prospective uncontrolled studies, and four retrospective case series (Supporting Supporting information Table 1). The ELs are described in Figure . Seven studies were excluded due to overlapping patient populations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation